Efektifitas Program PELITA terhadap Ekspansi Leksikal Siswa Kelas V Sekolah Dasar - Alfian Qori Irsandi; Nanang Rahman; Leny Anugra Safutri; Sintia Khairani; Siska Marthaleza; Sukaesi Sukaesi (Universitas Muhammadiyah Mataram, 2026)
Indonesia's low literacy achievement in PISA 2022 underscores the urgency of evidence-based literacy programs at the regional level. This study aims to analyze the effectiveness of the PELITA (Literacy and Character Education) program on the lexical expansion of fifth-grade students at SDN 1 Labuapi, West Lombok Regency. A quantitative One-Group Pretest-Posttest design was employed (n=34). Data analysis included the Shapiro-Wilk normality test, statistic descriptive, Paired Sample T-Test, and N-Gain Score. Results showed a mean score increase from 9.65 to 14.88, with t = -46.672 and significance of 0.000 (p < 0.05), confirming a significant effect of PELITA on students' lexical expansion. The N-Gain Score of 0.5182 (51.82%) indicates moderate effectiveness. This study concludes that PELITA is a regionally-initiated literacy intervention with a strong empirical basis, consistent with national and international literacy research findings.